Real-Time Assessment of Pain and Physical Activity in Knee Osteoarthritis: The Moderating Roles of Self-Efficacy, Fear of Movement, and Locus of Control - Almaw, Rachel (University of Waterloo, 2025)
Knee osteoarthritis (OA) is a highly prevalent chronic musculoskeletal condition and growing health concern in Canada. Characterized by loss of articular cartilage in the joint and fluctuating pain, knee OA is a leading contributor to physical and psychosocial disability (Steinmetz et al., 2023). By 2041, knee OA will affect over 10 million Canadians, driven by an aging and obese population (Sharif et al., 2017). Physical activity (PA) is recommended for knee OA management to reduce pain; but pain is commonly cited as a barrier to engagement (Bannuru et al., 2019). The links between PA exposure and pain are unclear. Current assessment tools cannot capture the temporal relationship between pain and PA in knee OA, as each dynamically influences the other throughout the day. This dynamic relationship is further complicated by psychosocial factors, including fear of movement, self-efficacy, and locus of control, which are associated with altered pain perception and PA behaviour in knee OA (Bayrak & Alkan, 2025). Yet, their roles in shaping the temporal relationship between pain and PA remain unclear in real-world contexts. Objectives and Hypothesis The primary objective of this study was to determine whether psychosocial factors (fear of movement, self-efficacy, and locus of control) moderate the temporal relationship between pain and subsequent PA in knee OA. The secondary objective examined the reverse temporal association: whether these psychological factors moderated the effect of PA on subsequent pain. It was hypothesized that (1) pain would reduce subsequent PA, with higher self-efficacy and internal locus of control weakening this negative effect and higher fear of movement strengthening the association; and (2) PA would increase subsequent pain, with higher self-efficacy and internal locus of control weakening this positive effect and higher fear of movement strengthening the association. Methods This prospective cohort study used ecological momentary assessment (EMA) over nine days. Fifty community-dwelling adults who had symptomatic knee OA consistent with American College of Rheumatology clinical criteria participated. Exclusion criteria included other forms of arthritis, neurological conditions, active cancer treatment, non-nociceptive pain, or lack of a compatible smartphone for EMA.Participants reported knee pain intensity, duration, and analgesic use four times daily using an EMA approach, via scheduled prompts delivered using a smartphone application (m-Path). Participant could also initiate prompts, unscheduled, to report pain flares. A pain composite score was calculated using z-score standardization of pain intensity and duration with participant-specific means and standard deviations, providing a novel within-person approach to characterizing knee OA pain. PA was continuously tracked using accelerometers (Actigraph wGT3X-BT) during waking hours. Psychosocial factors including fear of movement, self-efficacy, and locus of control were assessed through validated questionnaires at baseline. The primary objective examined whether the pain composite score influenced subsequent step count in the 90 minutes after EMA prompts, and whether this association was moderated by psychosocial factors (fear of movement, self-efficacy, locus of control). Generalized linear mixed models with Tweedie distributions and random intercepts examined these relationships, adjusting for age, gender, analgesic use, study day, prompt number, and prompt type. The secondary objective examined whether step count in the 90 minutes before EMA prompts influenced subsequent pain intensity, and whether this association was moderated by the same psychosocial factors. Linear mixed-effects models with random intercepts examined these relationships, adjusting for the same covariates. Results Complete data were available for 49 participants (64.8±7.2 years, 77% women) (1 accelerometer failure). These 49 participants reported moderate pain (KOOS Pain: 65.3±15.6), high daily activity (mean 11,661 steps/day), and mixed pain patterns (92% experienced both constant and intermittent pain). Average EMA compliance was 90%, with participants completing an average of 32 prompts over the study period. Valid accelerometer data was available for 96.6% of monitoring days. Fear of movement moderated the association between within-person pain composite score and subsequent step count (β = -0.0144, 95% CI [-0.0277, -0.0010], p = 0.035). Individuals with higher fear of movement showed a 4.9% greater step reduction per 1-SD increase (3.4 points on a 24-point scale) in fear of movement score. Self-efficacy for pain management also moderated this association (β = 0.0059, 95% CI [0.0018, 0.0100], p = 0.005). Individuals with higher self-efficacy showed a 6.8% smaller step count reduction per 1-SD increase (11.9 points on a 50-point scale) in self-efficacy score. Locus of control showed no moderation effect. In the reverse temporal direction, internal locus of control demonstrated a weak positive interaction with within-person step count on subsequent pain intensity (β = 0.000012, 95% CI [0.000002, 0.000022], p = 0.014). Individuals with higher internal locus of control experienced slightly greater pain intensity following higher step counts compared to those with lower internal locus of control. Self-efficacy for pain management demonstrated a significant main effect on subsequent pain intensity (β = -0.028740, 95% CI [-0.052042, -0.005439], p = 0.019). Individuals with higher self-efficacy reported lower pain intensity regardless of step count. Fear of movement showed no moderation or main effect. Discussion This study, using EMA and objective accelerometry, provides preliminary evidence that psychosocial factors moderate the temporal pain-PA relationship in adults with symptomatic knee OA. Those with higher self-efficacy for managing pain showed 6.8% smaller step reductions following greater pain; while those with higher fear of movement showed 4.9% greater reductions in step count after experiencing greater pain. In the reverse temporal direction, higher step counts were associated with increased subsequent pain intensity. Internal locus of control statistically moderated this association, though the interaction was very small and of uncertain clinical significance. Real-time assessment captured substantial within-person variability in pain and physical activity, including participant-initiated reporting of pain flares (77.6% of participants). The small interactions likely reflect considerable heterogeneity due to unmeasured contextual environmental factors. These findings suggest that self-efficacy, fear of movement, and locus of control may influence how individuals with knee OA respond to pain in daily life. While larger and more diverse samples are needed to establish clinical significance, these results suggest that self-management interventions targeting these factors and personalized pacing strategies during pain-free periods may help individuals with knee OA maintain activity despite pain fluctuations.
Keywords: osteoarthritis; ecological momentary assessment; physical activity; psychosocial factors